Spatial variation of the aerosol index for the Department of Junín - Angeles Vasquez , Roberto Julio (2022)
In this work, the spatial dynamic behavior of the aerosol index for the department of Junín is exposed. The basic information for the development of this research is satellite data obtained from NASA. The AURA satellite that has the OMI sensor installed has been monitoring the aerosol index (AI) since October 2004-2018. The satellite observations are as a whole a historical series of the concentration of the index, the data also have geographic coordinate information, which is why it was used to evaluate and simulate the spatial behavior using Kriging's spatial interpolation methodology. Where the greatest amount of suspended particles is observed both in the dry and wet season in the urban area that belongs to the province of Huancayo.